(untitled) (Medical Forum Monthly, 2024)
Objectives: To determine changes in root canal curvature after preparation with manual or rotary instrumentation technique and to determine maintenance of working length by either manual or rotary instrumentation technique. Study Design: Experimental study Place and Duration of Study: This study was carried out at Aga Khan University Hospital over a period of six months. Materials and Methods: Mandibular molars, extracted due to caries or periodontal reasons and mesiobuccal canals, with curvature between 20- 400 were included. In Group A preparation was carried out with ProTaper instruments and in group B with manual NiTi files. An ISO #15 NiTi file was placed in the canal and radiograph taken to determine working length, radiograph was scanned, print made and canal curvature determined. Upon completion of preparation, radiograph with #30 NiTi file was taken and working length assessed. Same radiograph was scanned, and changes in curvature were assessed by comparing preoperative and postoperative prints. Data analysis was done with SPSS version 14.0 and Paired and Independent sample t tests. Results: Difference in Pre and Post operative root canal curvature was lower in ProTaper group, but not satisfactorily significant. Working length was better maintained in ProTaper group as compared to group prepared with Manual Ni-Ti instruments. Conclusion: ProTaper instrumentation technique maintained working length better than manual instrumentation technique. No difference in operative curvature was observed, although difference was smaller in ProTaper group.